DONGÉNG GEBER-GEBER HIHID AING KARYA WAHYU WIBISANA JEUNG DONGÉNG BUDAK PAHATU LALIS KARYA KI UMBARA PIKEUN BAHAN AJAR MACA DONGÉNG DI KELAS VII SMP : Ulikan Struktural jeung Sastra Bandingan - Delpia Sinta Rahayu, _ (2022)
THE GEBER-GEBER TALE OF HIHID AING BY WAHYU WIBISANA AND THE DONGÉNG BUDAK PAHATU LALIS BY KI UMBARA FOR LEARNING MATERIALS FOR READING FALLS IN CLASS VII SMP (Structural Ulikan and Comparative Literature) Delpia Sinta Rahayu ABSTRACT This study aims to analyze and describe; (1) the structure of the story in the tale of Geber-Geber Hihid Aing and the story of Budak Pahatu Lalis which consists of the theme, plot, setting, and actors; (2) Comparison of structures in the story Geber-Geber Hihid Aing and the story Budak Pahatu Lalis; (3) The results of the study will be used as an alternative material for learning to read fairy tales in class VII SMP. This research method is descriptive qualitative using structural and comparative literature. The technique used in this research is document study. The results of the study: (1) the theme in this fairy tale is love between brother and sister. The plot used by each fairy tale is a forward plot. The setting in each fairy tale is the setting of place, setting of time and social setting; (2) the comparison of the Geber-Geber Hihid Aing fairy tale by Wahyu Wibisana and Ki Umbara Budak Pahatu Lalis fairy tale is similar until there is a difference because the dominant story of the Budak Pahatu Lalis fairy tale is longer. (3) the tales of Geber-Geber Hihid Aing and the fairy tales of Budak Pahatu Lalis can be used as alternative materials for learning to read fairy tales, because they meet several standard criteria for choosing teaching materials. Keywords: Comparison of fairy tales, fairy tales, structural, learning materials.